Aegla nebeccana n. sp. (Crustacea, Aeglidae) from Ivaí Basin, Paraná, Brazil - Trombetta, Alana De Souza; Páez, Fernanda Polli; Santos, Sandro; Teixeira, Gustavo Monteiro (Zootaxa, 2019)
A new species of freshwater anomuran, Aegla nebeccana n. sp. (Decapoda: Aeglidae), is described from the Ivaí River sub-basin, a tributary of the Paraná River Basin, in Paraná state, southern Brazil. The species is illustrated in detail with drawings and photographs. It can be distinguished from its congeners based on both morphological and molecular evidence. Morphologically, the new species resembles Aegla meloi Bond-Buckup & Santos, 2015 by the general shape of the carapace and chelipeds, but differs by having a developed protograstic lobe and by the cheliped ischium ornamentation. Aegla nebeccana n. sp. has pronounced protogastric lobes, similar to Aegla castro Schmitt, 1942 and Aegla schimitti Bond-Buckup & Buckup, 1994 but differs clearly from these in relation to the morphology of the cheliped palmar crest. Based on molecular analysis, A. nebeccana is sister species of Aegla parva Bond-Buckup & Buckup 1994.